Cancer of the sigmoid colon and antibodies. A puzzle. Issue 2 (April 2015) - Del Proposto, Gianpaolo; Antonelli, Maddalena; Cerrone, Paola; Bruno, Antoine; Costantino, Laila; Ricciardi, Edoardo; Rossi, Piero; Modica, Stella; Adorno, Gaspare
Abstract: In this work we describe the case report of a woman affected by cancer of the sigmoid colon and with a positive direct antiglobulin test (DAT) and indirect antiglobulin test (IAT). Case report with results: A meticulous medical history showed that the woman had been suffering from recurrent fetal loss. Then she had cardiac and coagulative problems. These data suggested a phospholipid syndrome. Conclusion: The patient had a medical history positive for a phospholipid syndrome and we think that this disease could explain the onset of the autoantibody.